The photocatalytic properties and construction of a WS2/MoS2/CdS heterojunction. (9th March 2022) - Qi, Shuyan; Zhang, Ruiyan; Zhang, Yiming; Zhang, Kaiyao; Xu, Huanyan
Abstract : The as-prepared WS2 /MoS2 /CdS composite heterojunction semiconductor exhibited high photocatalytic activity when degrading organic pollutants under visible light illumination. Abstract : WS2 /MoS2 /CdS (WMC), a photocatalyst with excellent photocatalytic performance, was synthesized via a coprecipitation hydrothermal method, and WS2 /MoS2 was loaded on the CdS surface. The addition of WS2 /MoS2 reduced the bandwidth of CdS, with lower electron–hole complex efficiency. When the mass ratio of WS2 /MoS2 is 5%, the photocatalytic efficiency of the photocatalyst is 98.15% after 240 min. The reaction rate constant of 5%-WMC is 0.01866 min −1, which is 6.17 times higher and 2.47 times higher than those of CdS and WS2 /MoS2, respectively. Capture agent tests showed that the active groups of the photocatalytic degradation process were O2 − ˙ and h + . The catalytic activity remained relatively stable over four experimental cycles.